Let’s Play! Engaging College Students in Mini Play Sessions, Perspectives, and Reflections - Winter, Marna (Teaching and Learning Inquiry, 2025)
This in-progress study explores the integration of play sessions into higher education classrooms as a strategy to reduce student stress and enhance overall well-being. With increasing levels of stress and mental health challenges among college students, faculty often struggle with providing adequate support, particularly as most are not trained mental health professionals. Through initial play sessions conducted in two different courses, students reported significant shifts from negative emotions, such as stress and overwhelm, to more positive states of happiness, excitement, and calmness. This aligns with existing research suggesting that structured play and wellness activities can improve mental health and reduce stress. The study also considers the potential for play sessions to offer a low-barrier, creative approach for faculty to foster a more supportive and engaging learning environment. Over the next academic year, routine play sessions will be implemented across five courses, with pre- and post-surveys used to assess their impact on student stress levels, focus, readiness for class, and overall engagement. The findings from this study aim to contribute to the growing body of research on wellness pedagogy, offering insights on the long-term benefits of integrating play into higher education settings. Further exploration is needed to systematically gauge the levels of impact over time and determine the broader implications of this approach for student well-being and academic success.